2004
DOI: 10.1111/j.1470-6431.2004.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer education: creating consumer awareness among adolescents in Botswana

Abstract: Senior secondary schools’ students in Botswana were studied to determine their awareness of consumer rights and responsibilities and their perceptions of consumer behaviour and consumer education. Recommendations will inform the refinement of consumer education teaching in Botswana as well as other secondary education programmes. A questionnaire suitable for this study was used to collect data. Responses from 3107 students were received. Descriptive statistical analysis was used to determine frequencies and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 3 publications
2
16
0
1
Order By: Relevance
“…The researcher in question states in his study of conscious consumerism that the students got high scores from the scale. Besides, in their study Makela and Peters (2004) indicate that consumer education has a positive impact on students' awareness of consumer rights and responsibilities. In addition; in his study, Ekström (2007) (Ferman, 1993).…”
Section: The Results Of the Research Showed That Thementioning
confidence: 99%
“…The researcher in question states in his study of conscious consumerism that the students got high scores from the scale. Besides, in their study Makela and Peters (2004) indicate that consumer education has a positive impact on students' awareness of consumer rights and responsibilities. In addition; in his study, Ekström (2007) (Ferman, 1993).…”
Section: The Results Of the Research Showed That Thementioning
confidence: 99%
“…This is a vital tool for consumer protection. As suggested by Makela and Peters (2004) and Gallagher (2002) consumer education and awareness would assist in developing responsible business behavior in the Nigerian electricity market.…”
Section: Discussionmentioning
confidence: 99%
“…At the African level, the example of Botswana and Kenya are quite instructive. In Botswana, consumer education is incorporated into the secondary school and university educational curriculum since 1990 (Makela & Peters, 2004). While consumer education is a priority to the UN, the EU and even in some African countries such as Botswana, it is not the case in the Nigerian context.…”
Section: Consumer Educationmentioning
confidence: 99%
“…In this context, children with basic consumer rights need to be educated on conscious consumption to make informed and conscious purchasing decisions (Consumer Affairs Victoria, 2003;Sánchez, Campa & Hernández, 2008). This education also aims to ensure that children engage in responsible consumption and use their economic resources responsibly, to improve their consumption-related knowledge and skills, to raise their awareness of sustainable consumption and to teach them how to claim their rights as consumers (Makela & Peters, 2004;McGregor, 2005;Kayali, 2008;Kaynak & Akan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Consumer education, which is one of the crucial topics in education, has been addressed in various studies. In related studies, consumer education was found to be effective in raising students' awareness of consumer rights and responsibilities (Makela & Peters, 2004;McGregor, 2010;Danilane & Marzano, 2014) and preventing conspicuous consumption (Unay, 2012). In addition, it has been reported that children whose awareness is raised during consumer education at school are effective in their parents' purchasing decisions (Ekström, 2007).…”
Section: Introductionmentioning
confidence: 99%